Less Is More: Evaluating the Benefits of Minimally Invasive Spinal Surgery - Ali A. Mohamed; Rakan Alshaibi; Steven Faragalla; Garrett Flynn; Asad Khan; Emma Sargent; Youssef Mohamed; Camberly Moriconi; Cooper Williams; Zev Karve; Daniel Colome; Phillip Mitchell Johansen; et al. (Life)
This review aims to explore the evolution, techniques, and outcomes of minimally invasive spine surgery (MISS) within the field of neurosurgery. We sought to address the increasing burden of spine degeneration in a rapidly aging population and the need for optimizing surgical management. This review explores various techniques in MISS, drawing upon evidence from retrospective studies, case series, systematic reviews, and technological advancements in neurosurgical spine treatment. Various approaches, including endonasal cervical, transoral cervical, transcervical, mini-open/percutaneous, tubular, and endoscopic techniques, provide alternatives for current approaches to a range of spinal pathologies. The main findings of this review highlight potential advantages of MISS over traditional open surgery, including reduced complications, shorter hospital stays, and improved patient outcomes. Our research underscores the importance of adopting MISS techniques to optimize patient care in neurosurgical spine treatment.